Layout guide for Journal of Physics: Design and Research of Distributed Educational Resource Sharing Platform Based on IPFS. Issue 1 (July 2021) - Zhou, Qinghe; Lu, Ju; Yin, Hongjie; He, Dong
Abstract: In the age of information network, blockchain technology has become a key focus. With the integration of new technologies, blockchain covers many fields such as finance, social welfare, agriculture, smart cities, and education. At the same time, education has undergone fundamental changes along with the continuous advancement of technology, and under the impetus of blockchain and other technologies, "technology better empowers education" is an important goal of education informatization workers. Therefore, this article will explore its application scenarios in the field of "blockchain + education" based on blockchain and IPFS-related technologies and elaborate on how IPFS technology can improve the efficiency of educational resource sharing, optimize the process of sharing and dissemination of educational resources, promote the improvement of the quality of science education and build the application prospects of science education resource sharing.